Study on Induced Fermentative Methodology for the Production of Virgin Coconut Oil from two Cocos nucifera Varieties - Muthukkannan, N.; Balasaravanan, T. (International Journal of Scientific Research in Biological Sciences, 2020)
In this study, Virgin Coconut Oil (VCO) was produced from West Coast Tall (WCT) and Deejay Coconuts (DJ) under induced fermentative methodology by employing Saccharomyces cerevisiae and Lactobacillus plantarum (9511) strains. This production methodology was optimized with temperature, PH, Inoculum concentration and Fermentation end time. The VCO yielding efficiencies were compared from two strains. Among the four parameters in the study, the maximum yielding efficiencies were obtained from WCT coconuts employing L. plantarum (9511) at 40±1ºC temperature, 5.5±0.1 PH, 7% (w/v) Inoculum concentration and 60hrs of fermentation end time. In conclusion, it has been observed that proximate analysis of VCO showed within the standard limits and also WCT Coconuts in combination with L. plantarum offered higher yield and better fatty acid proportion than the DJ Coconuts.